Enlarged tensile strain at edge of flexible substrate due to anticlastic curvature. (March 2022) - Jo, Woosung; Lee, Tae-Ik; Kim, Taek-Soo
Abstract: Understanding the mechanical strain imposed on flexible electronics during bending is an essential consideration for the robust design of devices. In general, the bending behavior of flexible electronics is analyzed such that the cross-sectional mechanical strain distribution is the same along the width direction. However, even though a single curvature is applied to the cross section, the anticlastic curvature occurs along the width owing to the Poisson's ratio effect along the width. In this study, we analyze the effect of the anticlastic curvature on the maximum tensile strain of a flexible substrate because it is critical to the fracture of brittle films on the substrate. The strain distributions at the center and edge of a bent 75 μm-thick polyethylene terephthalate (PET) substrate are measured using the microscale digital image correlation (DIC) method. The anticlastic curvature effect on the maximum tensile strain of the bent substrate is analyzed through a three-dimensional finite element method (FEM) simulation. Results of DIC analysis and FEM simulation show that the maximum tensile strain at the edge of the substrate is larger than that at the center of the substrate owing to the anticlastic curvature. The enlarged tensile strain at the edge of a flexible substrate is experimentally validated by bending a laser patterned hard-coated PET substrate. Highlights: The tensile strain along the width of PET substrate under bending is studied. The maximum tensile strain at edge of PET is larger than that at center of PET. The strain difference is attributed to the anticlastic curvature occurrence at edge. Enlarged maximum tensile strain at edge is experimentally validated by DIC analysis.